2015
DOI: 10.1007/s11999-014-3819-z
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Erythropoietin Alpha Reduces Postoperative Transfusions in THA and TKA but May Not Be Cost-effective

Abstract: Level III, therapeutic study. See Guidelines for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 35 publications
1
38
1
Order By: Relevance
“…Nevertheless, and in spite of the differences between both studies, in ours, we did not detect any supplementary benefit in RBC transfusion reduction, in the subgroups of intracapsular HF, or in those patients with highest Hb levels (in our case those with inclusion Hb level ≥ 115 g/L). Data from our study also contrast with the established benefit of preoperative EPO and IV iron in patients undergoing elective major orthopedic procedures . Nevertheless, results obtained in the previous trials are difficult to extrapolate to patients with HF.…”
Section: Discussioncontrasting
confidence: 89%
“…Nevertheless, and in spite of the differences between both studies, in ours, we did not detect any supplementary benefit in RBC transfusion reduction, in the subgroups of intracapsular HF, or in those patients with highest Hb levels (in our case those with inclusion Hb level ≥ 115 g/L). Data from our study also contrast with the established benefit of preoperative EPO and IV iron in patients undergoing elective major orthopedic procedures . Nevertheless, results obtained in the previous trials are difficult to extrapolate to patients with HF.…”
Section: Discussioncontrasting
confidence: 89%
“…Previous authors have recommended preoperative autologous blood donation in TSA for patients with preoperative hemoglobin levels between 110 and 130 g/L [30]. In the setting of TKA and THA, various preoperative hemoglobin optimization strategies have been studied including autologous and allogeneic blood transfusion protocols, erythropoietin alpha, and tranexamic acid with varying degrees of success and cost-effectiveness [3,13,16,18,20,34,48]. Having used a large multicenter database, our study supports and extends previous results with our finding that a preoperative hematocrit \ 38% is an independent predictor of transfusion.…”
Section: Discussionmentioning
confidence: 99%
“…In an unrestricted transfusion standard study, Bedair et al . demonstrate that erythropoietin could increase the postoperative Hb level ( P < 0.001) and lower transfusion rates (0% vs 41%, P < 0.001) but increase healthcare costs ($2632 vs $2284). Another study found that erythropoietin reduced blood transfusion even under restrictive transfusion criteria.…”
Section: Preoperative Strategiesmentioning
confidence: 96%